Renewable Energy Sources and Analyzing the Wind Turbine Performance; a Review - lori, Erfan Shamsaddini; Leman, Zulkiflle (Ciência e Natura, 2016)
The potential of renewable energy resources has been investigated and its is shown that they can in fact fulfill most of the world’s energy demand. In this study renewable energy sources such as biomass, solar, wind, geothermal and hydropower are studied and provided with sustainable energy services, based on the available natural resources. In the past three decades wind and solar power system have developed rapidly in sales, while there was a decline in their capital cost and costs of electricity generated. This study shows that the transition to renewable –based energy systems are increasing and continues to improve their performance characteristic. The enhancement and utilization of renewable energy sources can increase diversity in energy supply market, help to secure long term supportable energy supplies, keeping the environment clean by reducing local and global atmospheric emissions, establish marvelous options too encounter specific energy service needs by helping to create new job opportunities especially in developing countries.